GESTIÓN DE TALENTO HUMANO EN LA EMPRESA “NICHIPER S.A” DE VENTANAS - CARPIO RIVAS, KARINA ELIZABETH (2018)
The company "NICHIPER" S.A. started in 2008, dedicated to home sales, is located in the province of Los Ríos, it covers the construction of 385 housing solutions, the execution is in charge of the construction company "CONVIVISA" S.A. who received a loan from the Ecuadorian bank of housing for three billion for the execution of the work. The houses are two stories, its sales price is $ 64,500 up to $ 66,500